2016
DOI: 10.1016/j.coche.2016.08.017
|View full text |Cite
|
Sign up to set email alerts
|

Modeling solid-electrolyte interfacial phenomena in silicon anodes

Abstract: Silicon shows promising characteristics to replace graphite as the anode material in Li-ion batteries (LIBs). However addressing the volume changes in silicon during lithiation and the formation of the solid-electrolyte interphase (SEI) at the silicon-based anodes are essential to make this a practical technology. The electrolyte decomposition can lead to a continuous growth of the SEI layer; which in turn serves a double purpose: passivation of the anode surface and barrier for the Li + diffusion. Despite the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(33 citation statements)
references
References 51 publications
0
32
0
Order By: Relevance
“…SEI growth is faster forh igher currents because the SEI current increases with j int accordingt oE quations (25) and (27). The causef or the transition in time dependence is as hift from diffusion-limited to migration-limited growth.…”
Section: Ultra Long-termsei Growthmentioning
confidence: 99%
See 1 more Smart Citation
“…SEI growth is faster forh igher currents because the SEI current increases with j int accordingt oE quations (25) and (27). The causef or the transition in time dependence is as hift from diffusion-limited to migration-limited growth.…”
Section: Ultra Long-termsei Growthmentioning
confidence: 99%
“…[23][24][25][26] On the microscale, atomistic simulations were used to analyze the chemical structure, composition, and reactionso ft he SEI. [7,[27][28][29] On the mesoscale, detailed continuum modelss hed light on the processes at the electrochemical interfaces. [30][31][32] In these mesoscale models, it is well-established that transport processes limit SEI growth during long-term battery storage.T ransport limitations lead to ac apacity fade proportionalt ot he square root of elapsed time, that is, p t. Different mechanismsw ere proposed to explain this behavior, [6,33] including solvent diffusion, [2,[30][31][32][34][35][36][37][38][39][40] electronc onduction, [4,30,32,37,[41][42][43][44] electron tunneling, [31,36,45] and the diffusion of neutral lithium atoms.…”
Section: Introductionmentioning
confidence: 99%
“…Nano-structured Si can avoid Si fracture, but because of the high surface area, it must be optimized along with a chemically and mechanically stable SEI in order to avoid SEI mechanical-electrochemical degradation and to achieve high Coulombic efficiency. 45 In terms of lithium metal anode, dendrites, which can lead to short circuits and electronically disconnected lithium, is still an unresolved issue. 37,[39][40][41] The origin of the issue is the extremely active Li metal surface, as SEI has to form on Li surfaces.…”
Section: Solid Electrolyte Interphase (Sei) In Li-ion Batteriesmentioning
confidence: 99%
“…Leung and Budzien compared EC decomposition on the basal plane of lithiated graphite (LiC 6 ), terminated with =O, -OH and -H and found that C = O edges provide a larger driving force for EC reduction 62 The observation that EC is more inclined to decompose in the presence of oxygen/ hydroxyl termination is consistent with other simulation results. 96 Besides graphite, EC decomposition was simulated on Li, 57,60,97 Si, 45,64,98 and Sn 99 electrodes as well. Due to the lower potential of Li metal than graphite, the decomposition of EC on Li metal is spontaneous and much faster than that on LiC 6 surfaces.…”
Section: Ec Solvent Decomposition Mechanismmentioning
confidence: 99%
“…8,19,20 Lithium dendrite growth has been extensively investigated in the last decades, 21 but lithium dendrite growth is still almost inevitable during charge and discharge cycles of the battery. 22,23 Lithium dendrites growth has been detected at the solid-electrolyte interphase (SEI) cracks. 16,21 On the other hand, recently Zhang et al were able to produce dendrite free electrodes using FEC/LiNO 3 electrolyte, 24 and Mashayek et al 25 has reported Liion diffusion through the SEI of Li-metal batteries.…”
Section: Introductionmentioning
confidence: 99%